Functional and taxonomic significance of seed structure in Salix mucronata (Salicaceae) - E. M. A. Steyn; G. F. Smith; A. E. van Wyk (Bothalia: African Biodiversity & Conservation, 2004)
The polymorphic African willow, Salix mucronata Thunb., is a widely distributed African tree and a riparian rheophyte. Ovule-to-seed development is reported for Salix mucronata subsp. woodii (Seemen) Immelman. Contrary to some existing reports, the tuft of silky hairs enveloping the seed in Salix is derived from the funicle and not the placenta. The micromor- phological structure of the hilar aril and funicular-placental and arillate hairs is described and illustrated for the first time.Willow seeds are primarily wind-dispersed, but have additional characters, such as a hydrophobic seed coat and an unwet- table, hairy, hilar aril as specific adaptations for distribution by water, perhaps even chance dispersal by animal visitors to the riverine habitat. Seed adaptations linked to different dispersal strategies may account for seemingly marked differences in ovule/seed structure between Salicaceae S.  str. and related, mainly zoochorous flacourtiaceous taxa. recently classified with the former in a more inclusively circumscribed Salicaeae s.l.